Reader's digest Atlas of the Bible : an illustrated guide to the Holy Land - Gardner, Joseph Lawrence, 1933-; Frank, Harry Thomas (Reader's Digest Association, 1981)
Narrative, maps, photos, and other illustrations place Bible stories in a historical-geographic framework. Includes a gazetteer of around 900 biblical place names